Prostate cancer detection using MRI ultrasound fusion-guided biopsy compared with saturation biopsy in patients with prior negative biopsies in King Chulalongkorn Memorial Hospital - Suksupha, Kaureuk; Opanuraks, Julin; Sowanthip, Dutsadee (Insight Urology, 2019)
Background:Magnetic resonance imaging (MRI) ultrasound fusion-guided prostate biopsy (MRGB) and saturation biopsy (SB) are both alternative techniques to standard transrectal ultrasound-guided biopsy in the setting of repeat biopsy. Nevertheless, comparative evidence of the efficacy of both techniques remains unclear. Objective:To compare prostate cancer (PCa) detection between MRGB and SB in patients with history of at least one prior negative prostate biopsy and prostate-specific antigen (PSA) ≥4 ng/ml. Material and Methods:Between November, 2015 and December, 2018, a total 82 men with prior negative biopsies and persistent elevated PSA underwent MRGB combination with subsequent SB in our institution. Their charts were retrospectively reviewed. In our institution, MRGB was performed at the lesions scored 3-5 by Prostate Imaging Reporting and Data System (PI-RADS) on MRI. The primary outcome was the PCa detection. Secondary outcomes were the detection rate of significant PCa (Gleason ≥7) , histopathologic details of biopsy, complication rate. Sensitivity, specificity, negative predictive values (NPVs), and positive predictive values (PPVs) were reported. Results:of 82 men, 39 (47.6%) had PCa. Overall PCa detection rate were 37.8% by MRGB and 31.7% by SB (95% confidence interval for difference, -6.0% to 18.1%; p = 0.27). The estimated sensitivity of MRGB and SB for overall PCa detection were 79.5% and 66.7%, respectively. The highest positive rate was among PI-RADS score of 5 (80%), followed by score of 4 (26%) and 3 (12%). Conclusions:In setting of repeat biopsy, PCa detection rate by MRGB was better than SB insignificantly in our institution. MRGB was also found to have better sensitivity to overall PCa detection than SB.